HAK DAN KEWAJIBAN PEKERJA DALAM UNDANG-UNDANG KETENAGAKERJAAN - Nurhotia Harahap (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2020)
The world of labor in Indonesia experiences prolonged problems ranging from workers 'welfare to indications of the government's partisanship to foreign workers, then the main focus in this paper is how workers' rights and obligations are regulated in the Manpower Act using qualitative descriptive methods through studies literature in various books and journals related to employment.The finding of the author in this article is that government policies in dealing with labor rights and obligations are already regulated in labor laws, although there are still things that need to be revised to create more prosperous workers.